2012
DOI: 10.1017/s0025315412001269
|View full text |Cite
|
Sign up to set email alerts
|

Growth and reproductive cycle of Hypermastus tokunagai (Caenogastropoda: Eulimidae), an ectoparasite of the sand dollar Scaphechinus mirabilis (Clypeasteroida: Scutellidae) in the Seto Inland Sea, Japan

Abstract: Hypermastus tokunagai is a eulimid gastropod infecting the sand dollar Scaphechinus mirabilis. The eulimid is easily detached from the host and thus regarded as a temporary parasite. In this study, the growth and reproductive cycle of H. tokunagai were investigated using specimens collected from S. mirabilis in the western Seto Inland Sea, Japan. Newly recruited individuals of H. tokunagai appeared in early autumn and grew rapidly, while growth was retarded from mid-autumn to winter months. A second rapid grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…We found that males have the body whorl angular on the base and smaller size. This aspect is not conclusive for this species as noted by Matsuda et al (2012), but 1 reproductive structure like a penis was registered. In this work, contrary to what was mentioned by Rodríguez et al (2001), who observed the same color pattern in all N. nana specimens, the mantle color pattern of N. worsfoldi is not permanent.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We found that males have the body whorl angular on the base and smaller size. This aspect is not conclusive for this species as noted by Matsuda et al (2012), but 1 reproductive structure like a penis was registered. In this work, contrary to what was mentioned by Rodríguez et al (2001), who observed the same color pattern in all N. nana specimens, the mantle color pattern of N. worsfoldi is not permanent.…”
Section: Discussionmentioning
confidence: 67%
“…Several authors have done important research on ecological aspects of eulimids, but our knowledge is still fragmentary and the complex life history of eulimids is largely unknown (Matsuda et al, 2012). Will (2009) pointed out that a study of host-parasite interactions will be doubly useful by allowing general insights into parasite systems and by increasing the knowledge of eulimid natural history.…”
Section: Introductionmentioning
confidence: 99%
“…While they appear to be geographically widespread, Eulimidae are rarely found in great numbers in association with their hosts, hampering studies on their life history (Matsuda et al 2012). The collection of more specimens would provide opportunities for laboratory experiments (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Eulimid species in a single genus generally exploit hosts of the same echinoderm class (Warén 1984), suggesting that the other congeners may also parasitize (irregular) sea urchins. Previously known parasites of irregular sea urchins include the species of three other eulimid genera, Clypeastericola Warén, 1994, Hypermastus Pilsbry, 1899and Turveria Berry, 1956(Warén and Crossland 1991Warén et al 1994;Matsuda et al 2010Matsuda et al , 2013a. Those eulimids, however, appear to be distantly related to Haliella with rather different shell morphology (see Warén 1984).…”
Section: Taxonomymentioning
confidence: 99%